Probability Forecast Using Fan Chart Analysis: A Case of the Sierra Leone Economy - JACKSON, Emerson Abraham; TAMUKE, Edmund (Journal of Advanced Studies in Finance; Vol 9 No 1 (2018): JASF Volume IX Issue 1(17) Summer 2018DO - 10.14505//jasf.v9.1(17).04, 2018)
This article made use of ARIMAX methodology in producing probability forecast from Fan Chart analysis for the Sierra Leone economy. In view of the estimation technique used to determine best model choice for outputting the Fan Chart, the outcomes have shown the importance of Exchange Rate variable as an exogenous component in influencing Inflation dynamics in Sierra Leone. The use of Brier Score probability was also used to ascertain the accuracy of the forecast methodology. Despite inflation outcome is showing an upward trend for the forecasted periods, the probability bands (upper and lower) have also revealed the peculiarity of the Sierra Leone economy when it comes to addressing policy measures for controlling spiralling inflation dynamics.